Morski Jedwabny Szlak – Chiny potęgą morską? - Pająk, Maria (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Nowadays we can observe an increased activity of China in the field of international politics. It is mostly by the new project of Chinese president Xi Jinping called One Belt One Road. The paper will consist of geographical, political and economical reasons of creating Maritime Silk Road and will try to explain its meaning to the chinese economy. The author will also try to answer the question: Can we already call China a sea power? Considerations will be based on the theory of sea power created by Alfred Thayer Mahan. His theory has helped the United States to become world’s most dominant country and economic superpower. The author try to figure out if China wants to follow the same path as US did
Keywords: sea power; China; Mahan, Alfred Thayer (1840-1914); Sea Silk Road